Analisis Penerapan Model Pembelajaran Problem Based Learning Pada Pelajaran Biologi Materi Sistem Ekskresi Kelas X SMA Negeri 4 Binjai: (Analysis of the Application of the Problem Based Learning Model in Biology Lessons on the Excretory System Material for Class High School 4 Binjai) - Tambunan, Evenia; Sitepu, Sindi Clodia br; Witin, Theresia Adhellia; Arwita, Widya (BIODIK, 2024)
Problem Based Learning is a form of learning that gives students problems to solve, so that they can improve critical thinking skills and understanding of concepts. This research aims to apply how the application of the PBL learning model influences the learning process and students' understanding of excretory material in class 10 of SMA Negeri 4 Binjai. The research method used was direct interviews with Biology subject teachers, so that information was obtained about the implementation of PBL, its supporting factors and obstacles as well as its impact on students. The research results show that the application of PBL in learning excretory material has a positive impact on students' understanding, students become more active in both lesson and practical activities, more critical in analyzing problems, and more independent in finding solutions. Problem Based Learning adalah bentuk pembelajaran yang memberikan masalah problem kepada siswa untuk diselesaikan, sehingga dapat meningkatkan keterampilan berpikir kritis dan pemahaman konsep. Penelitian ini bertujuan untuk menganalisis bagaimana penerapan model pembelajaran PBL mempengaruhi proses pembelajaran dan pemahaman siswa terhadap materi ekskresi pada kelas 10 SMA Negeri 4 Binjai. Metode penelitian yang digunakan yaitu wawancara langsung dengan guru mata pelajaran Biologi, sehingga diperoleh informasi tentang pelaksanaan PBL, faktor pendukung dan kehambatannya serta dampaknya terhadap siswa. Hasil penelitian menunjukkan bahwa penerapan PBL dalam pebelajran materi ekskresi memberikan dampak yang positif kepada pemahaman siswa, siswa menjadi lebih aktif baik dalam kegiatan lestur maupun praktikum, lebih lebih kritis dalam menganalisis masalah, dan lebih mandiri dalam mencari solusi.